Analysis of Dengue and SARS-CoV-2 Coinfection in a Tertiary Care Hospital: A Retrospective Study - Vinayaka Korishetty; Pooja Rao; Suchitra Shenoy; Udayalaxmi Jeppu; Keerthiraj B. (Journal of Tropical Medicine)
Introduction. Coinfection of dengue virus and SARS-CoV-2 infections in dengue-endemic areas is a significant public health concern. Coinfections can result in severe illness. Hence, this study determines the incidence of dengue and COVID-19 coinfection for a better understanding of the clinical presentation, laboratory parameters, and outcomes including mortality. Methods. The patients admitted to two tertiary hospitals with RT PCR-proven COVID-19 infection and dengue positive by NS1 rapid antigen or IgM dengue ELISA for two years between January 2020 and December 2022 were considered. Clinical data were retrieved from medical records including the laboratory findings and outcomes of these patients. The categorical data were analyzed in the form of frequency and proportion. The quantitative data were analyzed in the form of mean, median, and proportion. Results. Out of 2301 confirmed dengue samples and 3718 confirmed COVID-19 samples, there were 14 cases of coinfection with the presence of COVID-19 and dengue infection at the same time. ICU admission of 14.2% and mean hospital stay of 7 days were noted. Mainly the symptoms reported were fever at 92.9%, myalgia at 35.7%, and headache, vomiting, and cough at 28.6%. The laboratory findings were elevated lactate dehydrogenase and C-reactive protein in 100% of patients, elevated ferritin in 92.9%, thrombocytopenia in 71.4%, elevated AST and ALT in 71.4%, and elevated D-dimer in 57.1% of patients. There was no effect on morbidity and mortality seen among coinfection. Conclusion. COVID-19 and dengue share similar clinical features and laboratory findings. Diagnosis of one disease cannot rule out the presence of other infections. There might be chances of misdiagnosis or missed diagnosis. Hence, it is important to stress about early detection using specific methods and confirmation of disease with timely management, as it is a potentially new dimension for public health concern and management.